Three‐dimensional full‐kinetic simulation of the solar wind interaction with a vertical dipolar lunar magnetic anomaly. Issue 9 (12th May 2016) - Deca, Jan; Divin, Andrey; Wang, Xu; Lembège, Bertrand; Markidis, Stefano; Horányi, Mihály; Lapenta, Giovanni
Abstract: A detailed understanding of the solar wind interaction with lunar magnetic anomalies (LMAs) is essential to identify its implications for lunar exploration and to enhance our physical understanding of the particle dynamics in a magnetized plasma. We present the first three‐dimensional full‐kinetic electromagnetic simulation case study of the solar wind interaction with a vertical dipole, resembling a medium‐size LMA. In contrast to a horizontal dipole, we show that a vertical dipole twists its field lines and cannot form a minimagnetosphere. Instead, it creates a ring‐shaped weathering pattern and reflects up to 21% (four times more as compared to the horizontal case) of the incoming solar wind ions electrostatically through the normal electric field formed above the electron shielding region surrounding the cusp. This work delivers a vital piece to fully comprehend and interpret lunar observations, as we find the amount of reflected ions to be a tracer for the underlying field structure. Key Points: In contrast to a horizontal dipolar LMA, a vertical dipole cannot form a minimagnetosphere A ring‐shaped weathering pattern is created and reflects up to 21% of the incoming solar wind ions The amount of reflected ions is a tracer for the underlying magnetic field structure